2005
DOI: 10.1103/physrevb.72.035217
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent mobility and recombination of the photoinduced charge carriers in conjugated polymer/fullerene bulk heterojunction solar cells

Abstract: Time-dependent mobility and recombination of the photoinducted charge carriers in conjugated polymer/fullerene bulk heterojunction solar cells. Physical Review Letters, 72 035217-1-035217-10. Time-dependent mobility and recombination of the photoinducted charge carriers in conjugated polymer/fullerene bulk heterojunction solar cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
206
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(216 citation statements)
references
References 48 publications
8
206
2
Order By: Relevance
“…The photogenerated carriers were then extracted by the triangular voltage pulse in reverse bias. 14 The faster carrier mobility can be calculated from photo-CELIV to be…”
Section: Resultsmentioning
confidence: 99%
“…The photogenerated carriers were then extracted by the triangular voltage pulse in reverse bias. 14 The faster carrier mobility can be calculated from photo-CELIV to be…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, as researchers seek to increase the efficiency of polymer photovoltaics and companies begin the process of upscaling this technology, increasing the thickness of the active layer of the BHJ becomes necessary due to the minimum film thicknesses that can be reproducibly fabricated from scalable printing processes (roll-to-roll printing, etc.). [6,69] Charge recombination has been studied via a variety of experimental methods, including time-of-flight (TOF), [70] steady-state current-voltage, [71][72][73][74] impedance spectroscopy, [75][76][77] photo induced charge extraction by linearly increasing voltage (photo-CELIV), [78] double injection currents, [79] transient absorption, and transient photovoltage measurements. [80,81] At applied voltages above the maximum power point and at the open circuit condition, bimolecular recombination reduces the current density and limits the fill factor, thereby decreasing of PCBM revealed that exciton hopping before charge separation only occurs in films with very low fullerene concentration and poor morphology, but does not play a role for favorable blends having ultrafast quantitative charge separation within 200 fs.…”
Section: Photoexcitation and Charge Transfermentioning
confidence: 99%
“…However, in other seemingly similar systems, recombination rates much closer to the Langevin model were observed. 14,26,27,[34][35][36] Even blends with very similar morphology can have dramatically different recombination rates.…”
mentioning
confidence: 99%